The Mechanism of Administrative and Legal Support for Ukraine’s Reconstruction: A Constitutional and Legal Model - Maryna Susak; Volodymyr Dikhtiievskyi; Petro Dikhtiievskyi; Oleh Bilous; Nataliia Kantor (Nusantara: Journal of Law Studies, 2026)
This study examines the mechanisms of administrative and legal support for the reconstruction of Ukraine during martial law and the post-war recovery period, with a particular focus on developing an effective public administration framework to ensure sustainable national reconstruction. The research aims to identify the institutional, regulatory, and governance mechanisms required to coordinate reconstruction policies, strengthen legal certainty, and enhance administrative effectiveness in crisis and post-conflict contexts. The study employs a comparative legal approach to analyze the experiences of several countries that successfully implemented large-scale post-war reconstruction, including Germany, Poland, Croatia, and Bosnia and Herzegovina. Through comparative analysis, the research evaluates the relevance and adaptability of foreign administrative and legal practices to the Ukrainian context. The findings demonstrate that effective post-war reconstruction depends on establishing an integrated administrative and legal system grounded in the principles of the rule of law, transparency, accountability, decentralization, and digital governance. The study identifies key challenges in institutional coordination, financial supervision, anti-corruption controls, strategic planning, and cooperation among state authorities, local governments, international partners, and civil society organizations. Furthermore, the research proposes a comprehensive institutional and legal reconstruction model consisting of regulatory, organizational, procedural, financial, digital, supervisory, and international coordination elements. The scientific contribution of this study lies in formulating a multidimensional administrative and legal framework that provides both theoretical and practical guidance for strengthening public governance mechanisms in post-conflict reconstruction and sustainable state recovery.